Education with interactif website media on patient compliance levels for implementation of post-odontectomy instructions - Khoirunnisa, Nani Mira; Laela, Dewi Sodja; Fatikhah, Nurul; Heriyanto, Yonan (Journal Center of Excellent : Health Assistive Technology, 2024)
Introduction: Patient compliance with post odontectomy instructions is one of the factors that determine postoperative success. Lack of patient knowledge can interfere with the healing process and cause complications. Instructions given verbally often make patients less aware of post-operative care. Interactive website media through gadgets can be used as a tool to increase patient knowledge as an effort to prevent complications. The purpose of the study was to determine the effect of providing education with interactive website media on the level of patient compliance with post-odontectomy instructions. Methods: The type of research used is pre-experiment research with Post Test Only With Control Group Design. Sampling using Accidental Sampling technique obtained as many as 30 people. The variables in the study were interactive website media and compliance. Hypothesis testing using mann whitney U. Results: The results showed a difference in the level of compliance after being given education through interactive website media between the intervention group (80%) and the control group (53.35%).  Mann Whitney U analysis showed that there was an effect on the provision of education with interactive website media on the level of patient compliance with the implementation of post odontectomy instructions p value = 0.049 (p < 0.05). Conclusion Interactive website media can improve patient compliance with instructions given at post odontectomy. Odontectomy patients become more aware of the importance of carrying out postoperative instructions to prevent complications